Historical record of upwelling-favorable winds in Southern Benguela 1833–2014 - David Gallego; Ricardo García-Herrera; Folly Serge Tomety; M. Carmen Álvarez-Castro; Cristina Peña-Ortiz (npj Climate and Atmospheric Science)
Abstract As a result of the high volume of maritime traffic along the coasts of Namibia and western South Africa, mariners recorded numerous in-situ wind observations since early times. Many of these historical data are currently available through the International Comprehensive Ocean-Atmosphere Data Set (ICOADS). Here, we make use of these historical data to develop an instrumental index for the characterization of the upwelling-favorable winds over the southern Benguela Upwelling System from 1833 to 2014. Our results suggest that upwelling in this region has increased since the mid-1980s, in good agreement with previous research. However, when the entire period is considered, our index does not evidence a long-term trend but a multidecadal variability with an oscillation period between 20 and 30 years. We found a significant influence of ENSO exerted through the modulation of the position of the South Atlantic high-pressure system. However, this teleconnection may be highly non-stationary.